Transfer in a conflict model as a reason for (unconditional) basic income - Marcel Franke (Albert-Ludwigs-Universität Freiburg, Freiburg Institute for Basic Income Studies (FRIBIS), 2022)
In the discussion about a universal basic income, the dimension of conditionality comes up frequently in the context of work requirements for social security policies. In these exchanges one aspect that comes up frequently is the costs of a universal social policy. In this article we apply a conflict model to the case of a basic income that suggests incentives for a government to pay a transfer to reduce and prevent conflict. These incentives justify the costs of the transfer program. However, the property that reduces conflict potential is the conditionality to lay down your arms. We discuss the condition of obeying the law to establish peace and a functioning economy. We argue that this conditionality is inherent to any form of societal participation and is a prerequisite for any social policy. Thus, it does not reject unconditional programs. Further, we discuss ways in which the constitutional perspective and the New Ordoliberalism may justify such conditionality.
Keywords: 330; Unconditional basic income; universal basic income; conditionality; conflict economics; transfer; constitutional economics; New Ordoliberalism